2021
DOI: 10.21608/jsec.2021.171517
|View full text |Cite
|
Sign up to set email alerts
|

Citizen-Centric Approach to E-government: Can It Help in Overcoming the Digitalization Financing Obstacle? The Case of Electricity Meter in Egypt

Abstract: Citizen-centric Approach to e-government Ola AlSayed -Shadwa Esmat Accepted date 25/4/2021 ‫التجارة‬ ‫و‬ ‫لالقتصاد‬ ‫العلمية‬ ‫المجلة‬ 169 implementation, and financing of e-government services. It provides insights to policymakers and governmental units to choose an appropriate financing mode for constructing and operating egovernment projects. In addition to determining the target groups of the e-government service in advance, to facilitate the transformation from traditional to digital service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…This study proves the opposite, but it goes in line with the result of the study of Al Sayed, and Esmat (2021), where past experience with online government service had no effect on the demand for that service. This, in fact, is understandable by looking back at the data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study proves the opposite, but it goes in line with the result of the study of Al Sayed, and Esmat (2021), where past experience with online government service had no effect on the demand for that service. This, in fact, is understandable by looking back at the data.…”
Section: Discussionsupporting
confidence: 87%
“…The study by Al Sayed, and Esmat (2021) showed that age has a significant impact on the demand for the online service-younger respondents have a higher demand for the digital services than older ones. But surprisingly, the result of this study indicated that age has no significant effect on WTP or WTP amount.…”
Section: Discussionmentioning
confidence: 99%